Eudendrium album Nutting 1898 - Gravili, Cinzia; Vito, Doris De; Camillo, Cristina Gioia Di; Martell, Luis; Piraino, Stefano; Boero, Ferdinando (Zenodo, 2015)
Eudendrium album Nutting, 1898 Fig. 13 A–D See Schuchert (2008b) for a complete synonymy. Material examined. HCUS-S 0 15 (Hydrozoa Collection, University of Salento—fauna of the Salento Peninsula). Description (based on our own observations; Marinopoulos 1992; Marques et al. 2000a; Schuchert 2008b, 2012): Hydroid. Hydrorhiza as creeping, branching stolons; colonies stolonal or erect; hydrocauli monosiphonic, small and delicate, unbranched or little branched, perisarc smooth with some corrugated or annulated stretches at base of hydrocladia and hydranths; hydranths cup-shaped, somewhat tapering towards base, 1–20 hydranths per shoot (up to 50 possible); hypostome rounded, large; with around 17–22 tentacles. Gonophores as fixed sporosacs, females develop in one whorl of about six sporosacs on body of a normally developed hydranth, with unbranched spadix when mature; males 2–3 (mostly 2) chambered, arising as a single whorl from lower part of the hydranth body. Colours: perisarc of stem brown to yellowish, branches yellowish-brown fading to colourless; hydranths white to cream coloured. Cnidome. Heterotrichous microbasic euryteles on tentacles, almond-shaped; larger macrobasic euryteles (27.5–29.0 x 10.0–11.0 Μm), shaft in intact capsule in 4–5 coils that are oblique in relation long axis of capsule, confined to upper 2/3 of capsule. Habitat type. Occurs from the intertidal to about 1000 m depth on various substrates (Schuchert, 2012). Substrate. Stones, algae, bryozoans and other hydroids. Seasonality. In the Ligurian Sea (Boero & Fresi 1986) from September to May, in Salento waters in August (De Vito 2006; this study). Reproductive period. In the Ligurian Sea, reproductive colonies occur from October to March (Boero & Fresi 1986). Distribution. Mediterranean to North Atlantic (Marinopoulos 1992; Marques et al. 2000a; Bouillon et al. 2004; Gravili et al. 2008a; Schuchert 2008b). Records in Salento. Rare, at: Torre dell’Inserraglio, S.ta Caterina, La Strea, La Rotonda, Ponte del Ciolo (Presicce 1991); ...